2009
DOI: 10.1111/j.1469-0691.2009.03091.x
|View full text |Cite
|
Sign up to set email alerts
|

New therapeutic choices for infections caused by methicillin-resistant Staphylococcus aureus

Abstract: In recent years, a marked increase in the incidence of infections caused by methicillin-resistant Staphylococcus aureus (MRSA) has occurred in many countries. This review addresses the effectiveness and limitations of drugs classically used for the treatment of MRSA, e.g. vancomycin, and also newer anti-MRSA antimicrobials, e.g. second-generation glycolipopeptides, tigecycline, and beta-lactams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 302 publications
(314 reference statements)
0
9
0
1
Order By: Relevance
“…A more recent example of an antibiotic associated with a potent antibiofilm effect is that of daptomycin. This bactericidal cyclic lipopeptide has an in vitro spectrum against Gram-positive pathogens through calcium-dependent disruption of membrane function, leading to potassium ion leakage and inhibition of DNA, RNA, and protein synthesis (224,225). In vitro studies suggested that daptomycin may quickly penetrate S. epidermidis biofilms, that it is effective against biofilms, and that it is bactericidal against stationary-phase and nondividing S. aureus (225)(226)(227)(228).…”
Section: Currently Used Approaches Do Not Specifically Target Biofilmmentioning
confidence: 99%
“…A more recent example of an antibiotic associated with a potent antibiofilm effect is that of daptomycin. This bactericidal cyclic lipopeptide has an in vitro spectrum against Gram-positive pathogens through calcium-dependent disruption of membrane function, leading to potassium ion leakage and inhibition of DNA, RNA, and protein synthesis (224,225). In vitro studies suggested that daptomycin may quickly penetrate S. epidermidis biofilms, that it is effective against biofilms, and that it is bactericidal against stationary-phase and nondividing S. aureus (225)(226)(227)(228).…”
Section: Currently Used Approaches Do Not Specifically Target Biofilmmentioning
confidence: 99%
“…According to the study researchers, use of these doses of oritavancin for S. aureus, although effective against pneumococci, warrants further analysis. A mild to moderate reduction in the potency of oritavancin by surfactant has been reported although the effect is much lower than that with daptomycin [40].…”
Section: Pharmacokineticsmentioning
confidence: 98%
“…El agente causal más frecuente es el Staphylococcus aureus en el 75% de los casos (7,8); hasta hace una década el 15% era meticilino-resistente y el 85% era sensible, pero en esta última década en algunas series hasta 40% son resistentes a la meticilina (5,9). Luego está el Staphylococcus epidermidis, principalmente cuando hay antecedente de instrumentación; Escherichia coli, si existe el antecedente de una infección urinaria; Pseudomona aeruginosa en pacientes que usan drogas endovenosas.…”
Section: Dr Eduardo Matosunclassified